The Works of Peter Schott, 1460-1490, Vol. I : Introduction and Text - Schott, Peter, 1458-1490 (University of North Carolina studies in the Germanic languages and literatures ;, 2020)
This first complete modern edition of Peter Schott's Lucubraciunculae opened a treasure-trove of information to students of German literature, historians of Humanism, folklorists, and theologians on its publication in 1963. Also included in this volume are the De mensirus syllabarum epithoma and a letter in German to Schott's sister Anna. Schott's works shed light on social, historical and religious questions of the time and are valuable documents of the Northern Renaissance.